A Estudante nos guia para a “Guerra dos Cinco Dias”: vestibulares da UFS entre 1970-1980 - Marinho, Danielle Virginie Santos Guimarães (2023)
In June 1980 the painter Jenner Augusto delivered to the Federal University of Sergipe a panel titled Instrução, Cultura, Ciência e Arte (Instruction, Culture, Science and Art), set at the rectory entrance hall since then. Considering the high historic potential that impregnates the narrative illustrated by the panel, this thesis dedicates itself to the knowledge of one of the themes that emerge from the analysis of the images at hand: the access to the Federal University of Sergipe (UFS) through the entrance exam then known as vestibular, between 1970 and 1980. The periodization refers to the year of 1970, when the UFS adapted its vestibular to the determinations of the University Reform on 1968, and also to the publication of the Ministerial Decree 321/1980, that determined substantial changes to vestibular across the country. The installation of the panel in 1980, is also remarkable because the depicted object derives from the interpretation of the figure of the student that composes the panel created in that same year. This is a research in the fields of History and Education and, as such, the methodological procedures employed were markedly related to these fields. Therefore, it arises as the result of a qualitative, historic, stemmed from critical and documentary analysis of sources, as well as bibliographic and biographical searches, in addition to interviews and iconographic studies. To achieve the main objective, which is to analyze stories of access to the UFS (1970-1980) from issues aroused by the visual narrative in “A estudante” (The Student), by means of the appreciation of publications about the UFS’s vestibular in print media, the following specific objective were drafted: to present stories that emerge from the semiotic analysis of the scene called “A estudante”, which integrates the panel Instrução, Cultura, Ciência e Arte; to measure the impacts of UFS’s vestibular based upon Sergipe’s print media coverage; to know the environment of preparation courses for vestibulandos (students in preparation for the vestibular exam), through the statements of the teachers and founders of private vestibular exam preparation courses in Aracaju. Likewise, it is understood that “A estudante” is a pictorial representation of a vestibulanda — central character on the issue of the access to higher education — and her presence in Jenner Augusto’s visual narrative means that the panel conceives UFS in its universal meaning (teaching, research and extension) when considering the vestibular as the point of origin of the academic cycle. This work investigates the hypothesis that during the decade of the 1970’s, the press coverage about the “Guerra dos Cinco Dias” (Five Days’ War), as the print media in Sergipe called the UFS’s vestibular period, produced a volume of information that makes it possible to historically gauge the expectations created by the exam. Finally, this thesis is built upon the elaboration of the meaning of the scene through the perspective of semiotic analysis, taking for reference Peirce (2015), whose methodological principles embrace the confrontation of initial perceptions with meanings attributed according to the analysts’ individual repertoire; the debate of the concepts of Representation, Chartier (1991), intellectual, from Bourdieu (1996), generation, from Mannheim (1982); vestibulares and higher education, Franco (1985) and Souza (2015).